Raw data: Physiological and genetic characterization of heat stress effects in a common bean RIL population - Vargas, Yulieth; Mayor Duran, Victor Manuel; Buendia, Hector Fabio; Ruíz Guzman, Henry Alonso; Raatz, Bodo (International Center for Tropical Agriculture, 2020)
Physiological and genetic characterization of heat stress effects in a common bean RIL population